Mechanical determinants of forward skating sprint inferred from off- and on-ice force-velocity evaluations in elite female ice hockey players - Perez, J.; Guilhem, G.; Hager, R.; Brocherie, F. (European Journal of Sport Science, 2021)
This study aimed to investigate the correlations between players` mechanical capacities determined during off- and on-ice tests. Whole body force-velocity relationships were assessed in elite female ice hockey players (n = 17) during jumping [squat jump (SJ)], running (5 m and 30 m) and skating (5 m and 40 m) sprint tasks. Mechanical capacities estimates include relative maximal theoretical force (F0rel), velocity (V0), power (Pmaxrel), slope of the linear relationship between force relative to body mass and velocity (SFVrel), maximal horizontal component of the ground reaction force to the corresponding resultant force (RFmax) and minimal rate of decrease of this ratio (DRF). On-ice mechanical capacities (F0rel, Pmaxrel, RFmax and DRF) largely-to-very largely correlated with 40-m skating split time (r ranging from 0.82 for DRF to -0.91 for Pmaxrel; p < 0.001). Performance variables (SJ height, 30-m running and 40-m forward skating split time) and Pmaxrel demonstrated the largest associations between jumping, running and skating tasks (r ranging from -0.81 for 30-m sprint running time to 0.92 for SJ height; p < 0.001). Small (V0, SFVrel, DRF and force-velocity deficit) to very large (Pmaxrel) correlations (r ranging from 0.58 to 0.72; p < 0.05) were obtained between mechanical variables inferred from off- and on-ice force-velocity tests. The capacity to generate high amounts of horizontal power and effective horizontal force during the first steps on the ice is paramount for forward skating sprint performance. Mechanical capacities determined during forward skating sprint could be considered in ice hockey testing to identify fitness and/or technical/training requirements.